2017
DOI: 10.3390/ma10060629
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Photocatalytic CO2 Reduction with Water: A Review

Abstract: In recent years, the increasing level of CO2 in the atmosphere has not only contributed to global warming but has also triggered considerable interest in photocatalytic reduction of CO2. The reduction of CO2 with H2O using sunlight is an innovative way to solve the current growing environmental challenges. This paper reviews the basic principles of photocatalysis and photocatalytic CO2 reduction, discusses the measures of the photocatalytic efficiency and summarizes current advances in the exploration of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
90
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(92 citation statements)
references
References 163 publications
(204 reference statements)
0
90
0
2
Order By: Relevance
“…[6][7][8][9][10][11] As one of the most popular photocatalytic materials, TiO 2 is chemically stable, nontoxic and earth-abundant to be proverbially utilized for CO 2 photoreduction. As an emerging carbon allotrope, graphdiyne (GDY) features 2D characteristics and unique carboncarbon bonds.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11] As one of the most popular photocatalytic materials, TiO 2 is chemically stable, nontoxic and earth-abundant to be proverbially utilized for CO 2 photoreduction. As an emerging carbon allotrope, graphdiyne (GDY) features 2D characteristics and unique carboncarbon bonds.…”
mentioning
confidence: 99%
“…Photocatalysis consists of two parts – ‘photo’ and ‘catalysis’. This means that the change in reaction rate during the chemical transformation of reactants into products without being involved in the reaction that is driven by irradiation of light . Photocatalysts are the substances that facilitate the active surface sites for pollutant or reactant molecule to adsorb/adhere at its surface.…”
Section: Recent Advancement In the Area Of Disinfection Researchmentioning
confidence: 99%
“…Among photocatalytic materials, TiO 2 has attracted much attention in scientific research as well as commercial applications. TiO 2 is well‐known as an efficient photocatalyst in air and water purification, water splitting, and the disinfection of surfaces . It has been demonstrated that including TiO 2 in the composition of a surface coating is a good approach to fabricating self‐cleaning materials .…”
Section: Introductionmentioning
confidence: 99%